Patogênese das lesões associadas à intoxicação por Ramaria flavo-brunnescens em bovinos - Trost, Maria Elisa (2009)
The pathogenesis of the lesions of the Ramaria flavo-brunnescens poisoning in cattle was studied throughout a retrospective evaluation of selected tissues from nine spontaneous and four experimental cases of the disease. The pathogenesis of lesions observed in the tongue, esophagus, hoof, and tail was investigated analyzing microscopic lesions, histochemical and histochemical-ultrastuctural changes. Histochemical techniques utilized were Masson s Trichrome and Selective Oxidation of Keratin (SOK). The histochemicalultrastuctural study was acomplished throughout the Swift method under transmission electron microscopy. Hair shafts of the tip of the tail were analyzed under polarized light. Lesions of varying degrees of severity were observed. They were more severe in spontaneous than in experimental cases. In the tongue, most microscopic lesions showed keratinization defects, such as loss of the filiform papillae, thinning, irregular stratification, focal lamelar keratinization, and individual cell keratinization (dyskeratosis) in the dorsal epithelium. In the esophagus, there were thinness of superficial epithelium and multifocal ulcers. In the hoof, lesions were in the laminar stratum and characterized by different grades of fusion, shortness, multiple layers of non-keratinized cells in the laminar tip, irregular and discontinuous keratinization with nuclear persistency, individual cell keratinization with citoplasmic vacuolization of keratinocytes of the epidermal laminae. In the skin of the tip of the tail, changes could by separated in follicular wall lesions (affecting the outer [ORS] and the inner root sheets [IRS]) and changes of the hair shaft itself. The main changes observed in the follicular epithelium were disorganization, misalignment, and disceratosis of keratinocytes of the ORS. On tissue sections, main changes in the hair shafts showed irregular contour, tortuousness, and disintegration of shaft. Morphological changes similar to the ones observed on tissue sections and changes in polarizing patterns were seen on polarized light microscopy of hair shafts. Tissue sections stained by Masson s Trichrome technique (with picric acid) revealed defective hard keratinization of filliform papillae, of epidermal lamina of hoof, and of tail tip hair shafts. Sections stained by the SOK technique revealed strong loss of cistine contents, visualized as light staining of these same structures. On the histochemical-ultrastructural study of the hair cuticle, performed throughout the Swift technique under transmission electron microscopy, a low content of cistine was also observed. All changes observed in the keratinized structures studied, mostly in the hard keratin, showed defective keratinization. The morphologic study and the results obtained with SOK and Swift techniques showed that the defective keratinization results of low amounts of sulphur containing amino acids (cystine) in hard keratin structures. This is probably the main pathogenetic mechanism of the lesions observed in R. flavo brunnescens poisoning in cattle.